Bridging Open Science and Data Visualization: Evaluating the Usability of dataWASHES Dashboard - Gonçalves, Victor; Viana, Davi; Santos, Rodrigo; Araújo, Allysson Allex (Anais do Workshop sobre Aspectos Sociais, Humanos e Econômicos de Software (WASHES), 2025)
[Context] Open Science has gained traction in Software Engineering in recent years, driven by the growing need to promote transparency and collaboration. The dataWASHES initiative exemplifies this perspective by providing an API for accessing WASHES proceedings. [Problem] Despite its contributions, dataWASHES lacks an interactive data visualization tool, limiting its accessibility to a broader audience. [Objective] This paper presents and evaluates a dashboard for dataWASHES to enhance data analysis and usability. [Method] We conducted a qualitative inspection based on Tufte’s principles and usability testing with 28 participants using the System Usability Scale (SUS). [Results] The dashboard adhered strongly to Tufte’s principles, particularly minimizing non-essential elements. The SUS yielded a score of 91.25, with 96.4% of participants reporting high satisfaction and 100% willing to recommend the tool. [Contributions] This work contributes by (1) applying Tufte’s principles in Open Science dashboards, (2) emphasizing the importance of user-centered design and data visualization in the engineering of Open Science tools, and (3) improving dataWASHES with a dashboard that turns data into actionable insights.